2018
DOI: 10.1002/awwa.1054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Treatment on the Quality of Harvested Rainwater for Residential Systems

Abstract: Rainwater harvested from four pilot-scale roofs (concrete tile, green, metal, and asphalt-fiberglass shingle) was batch-chlorinated to a target total chlorine 10 min residual of 2 mg/L as Cl 2 and passed through an activated carbon filter after 24 h to simulate treatment in a residential system. Total coliforms (TCs) were not detected, and the total trihalomethane (TTHM) concentration was typically (>85% of samples) below the US Environmental Protection Agency maximum contaminant level (MCL) of 80 μg/L in chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…There are currently no national regulations for rainwater treatment for potable use. However, ARCSA/ASPE Guideline 63: Rainwater Catchment Systems , provides rainwater harvesters with suggested design criteria and water treatment goals. None of the physical and chemical parameters examined for the rainwater in this study exceeded US EPA health and aesthetic-based drinking water limits, if present.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are currently no national regulations for rainwater treatment for potable use. However, ARCSA/ASPE Guideline 63: Rainwater Catchment Systems , provides rainwater harvesters with suggested design criteria and water treatment goals. None of the physical and chemical parameters examined for the rainwater in this study exceeded US EPA health and aesthetic-based drinking water limits, if present.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has focused on chemical and microbial characteristics of rainwater prior to and immediately after treatment, ,,, but this study provides unique insights about the role of rainwater quality as it flows into and interacts with building plumbing. The results indicate that building operators should understand and be prepared to contend with the potential consequences of corrosion and metal release, as well as increased microbial proliferation following a water source transition between municipal water and rainwater.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a study by Fuentes-Galván et al 33 in Guanajuato, Mexico, concluded that further treatment was required before consumption. Keithley et al 34 found activated carbon filtration followed by chlorination produced high quality potable water. Therefore, on-site testing and maintenance of RHRW collection and storage systems is suggested before recommending strategies for safe non-potable and potable water use or consumption.…”
Section: Rainwater Rooftop-harvested Rainwatermentioning
confidence: 99%
“…LID devices, such as rain barrels, have long been used for rainwater harvesting in many parts of the world where annual rainfall is moderate to abundant (Australia—Rodrigo, Sinclair, & Leder, ; Huston, Chan, Chapman, Gardner, & Shaw, ; Wang & Blackmore, ; Bangladesh—Karim, ; Brazil—Pacheco, Gomez, Oliveira, & Teixeira, ; Europe—Palla, Gnecco, Lanza, & La Barbera, ; Malaysia—Lee, Mokhtar, Hanafiah, Halim, & Badusah, ; Nigeria—Aladenola & Adeboye, ; Korea—Han & Mun, ; Italy—Liuzzo, Notaro, & Freni, ; United States—Keithley, ; Fricano & Grass, ) as well as in areas with semiarid to arid regions with low annual rainfall (Bakir & Liang, ; National Institute of Hydrology, ; Li, Gong, & Wei, ; Kahinda, Rockstrom, Taigbenu, & Dimes, ) and as an alternative source for potable and nonpotable water use (i.e., lawn irrigation, crop production; Imteaz, Adeboye, Rayburg, & Shanableh, ; Thomas, Kirisits, Lye, & Kinney, ; Boers & Ben‐Asher, ). This reduces water bills and saves energy used to produce and transport water, thus making it a viable strategy for supplementing local water supply both in areas with higher or lower risk of water scarcity (Dallman, Chaudhry, Muleta, & Lee, ; Ruberto, Lee, & Bayer, ).…”
Section: Introductionmentioning
confidence: 99%